Assessment of medical records management practice at Al-Wahda Hospital in Derna city, Libya - Arhaim, Saria M.; Elzahaf, Raga A.; Ghayth, Rwan S. (International Journal Of Community Medicine And Public Health, 2023)
Background: Medical records support patient’s care, provide continuity in the event of a disaster and protect the interests of the organization and the rights of employees. The aim of the study was to assess medical records management at Al-Wahda hospital in Derna, Libya. Methods: A cross-sectional design was conducted using various health professions including records officers, medical doctors, nurses for various department and the admitting clerks. A sample of 71 participants was selected using convenience-sampling technique. Data was collected using a questionnaire from August to October 2019. Results: The study showed that there was poor management of medical records at Al-Wahda hospital. The study revealed that the medical records were found in paper format. It indicated that the policy in place is record management policy, and findings confirmed that the policies are not communicated to healthcare workers and professionals. Furthermore, control measures were mentioned by the hospital records administrator was storing of records in locked cabinets. Similarly, the hospital records administrator confirmed that patient records were kept for above 12 months, and methods of patient records disposal is manually by burning. The study also indicated that failure to have a computerization processes. Conclusions: The findings of the study recommended the use of policy guidelines in relation to the best practices of how medical records are managed; the use of electronic systems for opening, tracking and indexing of files; further a need to increase the number of record officers, training of records staff; and conducting regular records awareness workshops.